The Study of Manganese Superoxide Dismutase Val16Ala Genotypes and its Association with Helicobacter pylori in Peptic Ulcer Patients in Kermanshah City, West of Iran - Sohrabi, Nasrollah (Asian Journal of Pharmaceutics (AJP), 2018)
Background: One of the main causes of gastric ulcer and inflammation is Helicobacter pylori (H. pylori). This bacterium has a global spread. The objective of the present research is to evaluate the genotype relationship between manganese superoxide dismutase (MnSOD) Ala16Val and the risk of the gastric ulcer. Materials and Methods: This case–control research was conducted on 75 patients with gastric ulcer and 60 healthy individuals as a control. By using the kit, DNA was extracted from gastric paraffin blocks and control group blood samples. Polymerase chain reaction was implemented to detect glmM and MnSOD genes, and restriction fragment length polymorphism was used to examine MnSOD Ala16Val polymorphism. Results: The frequency of glmM gene in patients with gastric ulcer was positive and was 74.66%. Analyzing MnSOD Ala16Val polymorphism indicated that the A/V frequency was higher in both patient and control groups. In addition, the allelic analysis indicated that the allele A was significantly (Sig = 0.000) higher in the patient group compared to that in control group (Sig = 0.000). It also showed that the genotype Ala/Ala can increase the gastric ulcer rate by 32.3 times. Conclusion: This research indicated a positive relationship between the MnSOD Ala16Val gene polymorphism and gastric ulcer. Therefore, Ala/Ala genotype could be considered as a risk factor for gastric ulcer disease.